An exploratory study on the Manila Film Center : A basis for a public relations campaign - Beblana, Karen Viel P.; Cortez, Lesly Kray M.; Llamosa, Justin Harvey N.; Moreno, Maribeth S. and Tritam Peter Thairo P. 4 0 16; 5 (2016)
u
Thesis: (Bachelor of Mass Communication) - Pamantasan ng Lungsod ng Maynila, 2016.
Keywords: 2 -- 0; 6; 20; 20; 2